Menuju Sekolah Ramah Anak Holistik-Integratif Melalui Learning Organization - Puspitasari, Intan Nuyulis Naeni (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2017)
The facts about the increasingly turbulent cases of children make education. institutions more serious about running child-friendly schools (SRA). The term SRA contains a meaning that is still very abstract and needs technical-political arguments as well as patterns of systematic application to describe it. Therefore, through the learning organization (LO) with the theoretical approach of The Fifth Discipline Peter M. Senge and Organizational Learning Model Michael J. Marquardt can further produce visionmission alignment, the formation of mental models and system thinking, as a very integral part in building understanding and implementation of SRA in a more holisticintegrative manner. Because solving wholly various cases and integrated certainly cannot be done alone, cooperations with many parties, both in the scope of micro, meso, exo and macro are necessarily allied. This becomes a responsive step as well as preventive way against various acts of crime and violence in children around us